Indolethylamine-N-methyltransferase Polymorphisms: Genetic and Biochemical Approaches for Study of Endogenous N,N,-dimethyltryptamine - Dean, Jon G. (Frontiers in Neuroscience, 2018)
N,N-dimethyltryptamine (DMT) is a powerful serotonergic psychedelic whose exogenous administration elicits striking psychedelic effects in humans. Studies have identified DMT and analogous compounds (e.g., 5-hydroxy-DMT, 5-methoxy-DMT) alongside of an enzyme capable of synthesizing DMT endogenously from tryptamine, indolethylamine-N-methyltransferase (INMT), in human and several other mammalian tissues. Subsequently, multiple hypotheses for the physiological role of endogenous DMT have emerged, from proposed immunomodulatory functions to an emphasis on the overlap between the mental states generated by exogenous DMT and naturally occurring altered states of consciousness; e.g., schizophrenia. However, no clear relationship between endogenous DMT and naturally occurring altered states of consciousness has yet been established from in vivo assays of DMT in bodily fluids. The advent of genetic screening has afforded the capability to link alterations in the sequence of specific genes to behavioral and molecular phenotypes via expression of identified single nucleotide polymorphisms (SNPs) in cell and animal models. As SNPs in INMT may impact endogenous DMT synthesis and levels via changes in INMT expression and/or INMT structure and function, these combined genetic and biochemical approaches circumvent the limitations of assaying DMT in bodily fluids and may augment data from prior in vitro and in vivo work. Therefore, all reported SNPs in INMT were amassed from genetic and biochemical literature and genomic databases to consolidate a blueprint for future studies aimed at elucidating whether DMT plays a physiological role.